Comment on ‘Small sample GEE estimation of regression parameters for longitudinal data’ - Lunardon, N.; Scharfstein, D. (Statistics in medicine, 2017)
In longitudinal studies, the generalized estimating equation (GEE) estimator of the parameters of a marginal model is known to be consistent even if the working intra‐subject covariance matrix is incorrectly specified. Recently, a small sample correction for the bias of the GEE estimator has been proposed. We show that this correction formula relies on the correct specification of the working intra‐subject covariance matrix. We provide a revised formula that is valid under misspecification and develop the R package ‘BCgee’ to ease the practical use of the formula. Copyright © 2017 John Wiley & Sons, Ltd.